Financial Ratio Analysis At PT. Rico Putra Selatan Bengkulu City - Meliani, Nita; Effendi, Bahman; Yanti, Rina Trisna (Universitas Dehasen Bengkulu, 2025)
This research aims to analyze the financial performance of PT. Rico Putra Selatan in Bengkulu City using profitability and liquidity ratios. The method used is a descriptive quantitative approach with secondary data sourced from the company's financial statements for the 2022-2023 period. The profitability ratios calculated include Gross Profit Margin (GPM), Net Profit Margin (NPM), Return on Assets (ROA), and Return on Equity (ROE). Meanwhile, the liquidity ratios include Current Ratio (CR), Quick Ratio (QR), and Cash Ratio (CaR). The results show a contrasting performance:Profitability is excellent, with average values for GPM at 23.07%, NPM at 3.66%, ROA at 29.25%, and ROE at 32.4%. Most of these figures meet or approach the